2019
DOI: 10.1002/cam4.2705
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world outcomes of FOLFIRINOX vs gemcitabine and nab‐paclitaxel in advanced pancreatic cancer: A population‐based propensity score‐weighted analysis

Abstract: BackgroundIn Ontario, FOLFIRINOX (FFX) and gemcitabine + nab‐paclitaxel (GnP) have been publicly funded for first‐line unresectable locally advanced pancreatic cancer (uLAPC) or metastatic pancreatic cancer (mPC) since April 2015. We examined the real‐world effectiveness and safety of FFX vs GnP for advanced pancreatic cancer, and in uLAPC and mPC.MethodsPatients receiving first‐line FFX or GnP from April 2015 to March 2017 were identified in the New Drug Funding Program database. Baseline characteristics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
64
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 28 publications
11
64
0
1
Order By: Relevance
“…However, it was recently demonstrated that FOLFIRINOX was associated with longer OS than GnP in patients with unresectable locally advanced or metastatic PDAC (38). Moreover, FOLFIRINOX treatment was reported to decrease the frequency of lymph node metastasis (30,39), consistent with our results supporting the effectiveness of NAC in patients with node-positive pancreatic head cancer (19).…”
Section: Discussionsupporting
confidence: 90%
“…However, it was recently demonstrated that FOLFIRINOX was associated with longer OS than GnP in patients with unresectable locally advanced or metastatic PDAC (38). Moreover, FOLFIRINOX treatment was reported to decrease the frequency of lymph node metastasis (30,39), consistent with our results supporting the effectiveness of NAC in patients with node-positive pancreatic head cancer (19).…”
Section: Discussionsupporting
confidence: 90%
“…Although the clinical benefits produced by 5-FU are lower than those of gemcitabine, 5-FU is still widely applied in treating pancreatic cancer partly due to its lower toxicity [139]. In recent years, increasing evidence has shown that the FOLFIRINOX regimen (5-FU, leucovorin, irinotecan and oxaliplatin) can achieve longer overall survival than gemcitabine-based therapy, especially in patients with good status [140][141][142][143][144]. Compared with other chemotherapy regimens, the underlying mechanism of gemcitabine resistance is relatively well documented [131].…”
Section: Chemoresistance and Metabolismmentioning
confidence: 99%
“…However, liver abscesses diagnosis in cancer patients, in this study, were associated with a long hospitalization, with a mean hospital stay of 30.5 days (95% CI: 20.3-40.7 days). The diagnosis of liver abscesses in this group of patients was also associated with poor outcome [8][9][10][11]. In the entire study population, median OS was only 6 months (95% CI: 1-12 months); and the OS probability at 18 months was only 27%.…”
Section: Discussionmentioning
confidence: 76%